Amino acid substitutions in VP2, VP1, and 2C attenuate a Coxsackievirus A16 in mice. (January 2021) - Zhang, Gaobo; Hu, Bing; Huo, Yuqi; Lu, Jia; Guo, Jing; Deng, Mi; Li, Pengfei; Wang, Weishan; Li, Li; Meng, Shengli; Wang, Zejun; Shen, Shuo
Abstract: Coxsackievirus A16 (CVA16) is one of the major etiological agents of hand, foot and mouth disease (HFMD), a common acute infectious disease affecting infants and young children. Severe symptoms of the central nervous system may develop and even lead to death. Here, a plaque-purified CVA16 strain, L731-P1 (P1), was serially passaged in Vero cells for six times and passage 6 (P6) stock became highly attenuated in newborn mice. Genomic sequencing of the P1 and P6 revealed seven nucleotide substitutions at positions 1434 (C to U), 2744 (A to G), 2747 (A to G), 3161 (G to A), 3182 (A to G), 4968 (C to U), and 6064 (C to U). Six of these substitutions resulted in amino acid changes at VP2-T161 M, VP1–N102D, VP1-T103A, VP1-E241K, VP1-T248A, and 2C–S297F, respectively. P1-based infectious cDNA was generated to further investigate these virulent determinants. Independent reverse transcription-polymerase chain reaction (RT-PCR) amplifications for mutant constructions and plaque-purification of the P6 for isolation of variants were performed to determine dominant mutations and strains more related to attenuation. The virulent P1, attenuated P6, as well as a plaque purified strain (PP) and other four recombinant mutants, were inoculated into one-day-old BALB/c mice and the 50% lethal dose of each strain was determined. Comparison of virulence among these strains indicated that amino acid changes of VP1–N102D, VP1-E241K and 2C–S297F might be associated more closely with a high level attenuation of CVA16-L731-P6 than other mutations. Identification of novel residues associated with virulence may contribute to understanding of molecular basis of virulence of CVA16 and other enteroviruses. Highlights: The novel amino acid residues in Coxsakievirus A16 (CVA16) were identified to be associated with virulence in mice. A single mutation of CVA16 noncapsid protein resulted in a high level of attenuation. The attenuated CVA16 may be suitable to be developed as safe backbone for recombinant vaccine candidates against HFMD.